The Concept of Holistic Sustainability in the Representation of The Cultural Landscape of Sumberawan Temple - Titisari, Ema Yunita; Wulandari, Lisa Dwi; Wahid, Julaihi; Mourad, Raghad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
The implementation of the sustainable development paradigm requires the collaboration of various parties. This is not easy to achieve due to the conflict of interest and dominance of certain aspects. This study explores the concept of holistic sustainability within traditional communities in the context of water resource conservation, using the cultural landscape of the Sumberawan Site in Malang as a case study. The research contributes to the development of local-traditional knowledge, which has proven effective in supporting sustainable development initiatives. The methodology employs Claude Lévi-Strauss’s structuralism to interpret the conceptual meaning embedded in the cultural landscape of Sumberawan Temple. Syntagmatic analysis is used to examine the sequential elements within each ‘myth,’ while paradigmatic analysis investigates the relationships between interchangeable ‘myths.’ Pattern identification is conducted through a binary opposition model. The study finds that the preservation of the Sumberawan water source is rooted in the strengthening of spiritual beliefs and the holistic integration of social and environmental elements. The message of conservation is transmitted across generations through myths, folklore, cultural rituals, artifacts, and spatial arrangements.